Labial Vibrotactile Somatosensory Perception: A Pilot Study in Healthy Aging versus Young Adult Participants. Issue 2 (April 2014) - Etter, Nicole M.; van Meter, Emily M.; Andreatta, Richard D.
The purpose of this pilot study was to begin characterizing changes in labial vibrotactile somatosensation in healthy older adults as a foundational step in determining how changes in orofacial sensation can affect functional behaviors, such as speech and feeding. Labial vibrotactile perception capacity of healthy older adults ( n = 15) was compared to a cohort of healthy young adults ( n = 5). Vibrotactile inputs were delivered to the glabrous surface of the left lower lip at 5, 10, 50, and 150 Hz. A modified von Bekesy (staircase) method was used to identify participants' thresholds and response standard deviations for each test frequency. Consistent with findings in other body regions, a decrease in labial vibrotactile detection sensitivity was expected in healthy older adults. The threshold values for the 5 and 10 Hz test frequencies were higher in the older group and the differences in response standard deviations at these frequencies were statistically significant. This pilot study identified changes in labial perception among healthy older adults.